Analisis Kinerja Keuangan Menggunakan Du Pont System Pada Entitas Publik Sub Sektor Industri Departement Store - Fadilla Ayu Ferianti; Dwi Asih Haryanti (CV. ITTC INDONESIA, 2026)
This study aims to evaluate and analyze the financial performance of public entities, especially those engaged in the department store sub-sector listed on the Indonesia Stock Exchange in 2021-2023, using an analysis method, namely the Du Pont System. The Du Pont System is used to identify factors that affect profitability, operational efficiency, and asset utilization. The results of this study show that the financial performance of public entities in the department stores sub-sector listed on the Indonesia Stock Exchange in 2021-2023 has fluctuated. The company that has the best financial performance among other department stores companies is PT. Matahari Departement Stores because it can generate Net Profit margin, Return On Investment and Equity Multiplier values are above industry ratio standards.